The no functional equivalence between the electronic proof and the documentary proof: A reading from the Colombian procedural regulation [La no equivalencia funcional entre la prueba electrónica y la prueba documental: Una lectura desde la regulacion procesal colombiana] (2019)
The principle of functional equivalence constituted the vehicle so that the electronic proof could be entered into the civil trial with full efficacy and validity effects in order that the judge of civil process would admit them and evaluate them according to the standard established for the documentary proof. However, the electronic proof is far distance from the documentary proof, questioning severely the veracity of this principle of functional equivalence, and in turn, the effectiveness of the electronic proof in the civil trial. © 2019 Universidad de Talca.